"Culture of Identity" and "Identity of Culture" - Majić, Ivan, kroatist (Array, 2010)
In this paper I am interested in special relation between individual aspect of culture which is connected with identity, forms and narrative discourses that establishes it and the issue of common culture, reference to social aspects of culture. Problems between individual identity and common culture are complex and interlaced ; what is more, their meanings reflect always-already one another. (Hall) According to postcolonial theorist Homi Bhabha hybridity can be final consequence of locating culture in between and mimicry, as an inner strategy of the postcolonial subject, is final consequence of the same strategy where identity might be in between. Nevertheless, Stephen Adam Schwartz detects numerous paradoxes within cultural studies especially in relation between the terms “identity” and “culture”. As a consequence he sees methodological individualism in cultural studies as a form of ethnocentrism. Due to mutual conditionality between them, concepts of “identity” and “culture” are showing that the knowledge and power are inseparable.